O conteúdo da proibição contra a crueldade com os animais na Constituição Federal - Neme, Eliana Franco (2004)
The objective of that work is going to present a new understanding about the meaning of the conteudo of the constitutional precept that prohibits the cruelty with the animals. Faced with to constatação of the impact of the environmental degradation about the life of the planet, stayed evident that an indissiociabilidade exists between the elements that composes that environment, that, therefore should be preserved not barely in part, but as the all that really is. The task is dificil in the measure in that the questionamentos relatives the human superiority about the too members of that planet, specially the animals, were left them take care of a small installment of the philosophical community, and the humanity of a general form looks enough comfortable with the position. The Brazilian constitutional text, like this, upon protecting the animals against the cruelty, shows up a perspective presenter of that we are us directing for the reavaliação of our rights and you will must with the animals, that, at least, healthy our partners in the journey by that world